Cryoablation Combined with Left Atrial Appendage Closure: A Safe and Effective Procedure for Paroxysmal Atrial Fibrillation Patients - Zhongyuan Ren; Jun Zhang; Mengyun Zhu; Dongdong Zhao; Shuang Li; Haotian Yang; Yixing Zheng; Weilun Meng; Jingying Zhang; Yawei Xu (Cardiology Research and Practice)
Background. Catheter ablation combined with left atrial appendage closure (LAAC) was reported as a feasible strategy for atrial fibrillation (AF) patients with high risk of stroke or contraindications of oral anticoagulants. We aimed to observe the short-term safety and efficacy of combining cryoballoon ablation (CBA) with LAAC in paroxysmal (PAF) patients. Method and Results. From Jan 2016 to Dec 2017, 304 patients diagnosed with nonvalvular, drug-refractory PAF were included, who underwent either CBA alone (n = 262) or combined procedure (n = 42). Instant pulmonary vein isolation (PVI) with CBA was achieved in all patients, while successful LAAC achieved in 41 (97.6%) of combined procedure patients. 1-year freedom of AF rate was lower in combined procedure group (84.7% vs 70.7%, p=0.04), with unadjusted hazard ratio (HR = 1.97) and 95% confidence interval (CI) 1.03–3.77. However, the multivariate COX model revealed left atrial diameter (p=0.002, HR = 1.10, and 95% CI 1.04, 1.17), rather than procedure type (p=0.51, HR = 1.34, and 95% CI 0.57, 3.17), was the predictor for freedom of AF. Only 2 patients in the CBA group had stroke, contributing to the nonsignificant higher stroke incidence (p=1.00). Transoesophageal echochardiography (TEE) achieved in 35 patients (83.3%) showed complete occlusion with no obvious residual flow (>3 mm), Device-related thrombosis, or pericardial perfusion. All-cause mortality, rehospitalization, and complication rates were similar. Conclusion. Combining CBA with LAAC in a single procedure is a feasible strategy for PAF patients, with comparable short-term safety and efficacy to CBA alone.